PENGARUH PERCERAIAN ORANGTUA BAGI PSIKOLOGIS ANAK - Uswatun Hasanah (State Institute of Islamic Studies Batusangkar, 2019)
The purpose of this paper is to know the effect of parental divorce on children's psychological. The method used qualitative research with a case study approach. The subject in this study amounted to one pair by using a purposive sampling technique that is sampling where the researcher has determined the criteria for the research subjects. The results of this study indicate that divorced parents will have a psychological effect on the child including the child receiving less attention, protection, and love from his father and mother.